Перехід від галузевого до територіального принципу організації системи влади та управління в СРСР (на прикладі Станіславської області УРСР) - Редько, А.Г. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Анализируются и сравниваются отраслевой и территориальный принципы организации системы власти и управления в СССР. Рассматривается процесс перехода от отраслевого к территориальному принципу организации партийно-государственного управления в пределах Станиславской области УССР и законодательное обеспечение этого перехода. In this article the sectorial and territorial principles of the organization of the authority and administration system in the USSR (the Union of the Soviet Socialist Republics) are analyzed and compared. The process of conversion from sectorial to territorial principle of organization of the state communist party administration within Stanislav Region of the USSR (Ukrainian Soviet Socialist Republic) and legal ensuring of this conversion is researched.